Wear and corrosion properties of HVOF coatings from Superduplex alloy modified with addition of boron - Berger, José Eduardo; Schulz, Robert; Savoie, Sylvio; Gallego, Juno [UNESP]; Kiminami, Claudio Shyinti; Bolfarini, Claudemiro; Botta, Walter José (Elsevier, 2017)
Fe-based protective coatings are promising alternatives to replace large or expensive mechanical structures in aggressive environments, such as, in petrochemical industries. In this work, we have evaluated the corrosion and abrasive wear resistance of coatings produced by the HVOF thermal spray process using the commercial SAF2507 Superduplex alloy modified by the addition of 3.0 wt% boron. Three coatings were obtained from different metal powders produced by different routes (spray forming and high energy ball milling). The coatings had a partially amorphous structure containing a dispersion of nanocrystalline borides, such as Fe3B and (Fe,Cr)2B. The coatings showed significant improvement in abrasive wear resistance and preserved the high corrosion resistance of the commercial SAF2507 Superduplex alloy.
Keywords: Abrasive wear resistance; Corrosion resistance; High-velocity oxygen fuel (HVOF); Nanocrystalline borides; Partially amorphous structure; Superduplex alloy